2018
DOI: 10.1021/acsami.8b09819
|View full text |Cite
|
Sign up to set email alerts
|

Nanofunctionalized Stent-Mediated Local Heat Treatment for the Suppression of Stent-Induced Tissue Hyperplasia

Abstract: Current therapeutic strategies are insufficient for suppressing stent-induced restenosis. Here, branched gold nanoparticles (BGNP)-coated self-expandable metallic stents (SEMSs) were developed for a local heat-induced suppression of stent-related tissue hyperplasia. Our polydopamine (PDA) coating on SEMS allowed BGNP crystal growth on the surface of SEMSs. The prepared BGNP-coated SEMS showed effective local heating under near-infrared laser irradiation. The effectiveness of BGNP-coated SEMSs for suppressing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…AgNP-coated SEMSs were prepared using a bio-inspired surface modification process ( Scheme 1 ) [ 20 ]. The PDA layer was first coated onto the SEMS surface, and then AgNPs were grown on the PDA surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AgNP-coated SEMSs were prepared using a bio-inspired surface modification process ( Scheme 1 ) [ 20 ]. The PDA layer was first coated onto the SEMS surface, and then AgNPs were grown on the PDA surface.…”
Section: Resultsmentioning
confidence: 99%
“…The stents were 4 mm in diameter and 10 mm in length and had radiopaque markers at both ends. The AgNP coating was added to the surface of nitinol SEMSs using polydopamine (PDA) chemistry ( Table S1, Supplementary Materials ) [ 20 ]. Dopamine hydrochloride (1 mg/mL) was dissolved in 15 mL of 5 mM Tris buffer (pH 8.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological evaluation using H&E was based on the degree of submucosal in ammatory cell in ltration, the number of epithelial layers, the thickness of the submucosal brosis, and the tissue-hyperplasia-related percentage of the esophageal cross-sectional area of stenosis calculated as 100 × (1 − [stenotic stented area/original stented area]). 6,11 The degree of in ammatory cell in ltration was subjectively determined according to the distribution and density of the in ammatory cells, i.e. graded as 1, mild when there was occasional visible in ltration of single leukocytes; 2, mild-to-moderate when there was patchy in ltration of leukocytes; 3, moderate when coalescing leukocytes made individual loci indistinguishable; 4, moderate-to-severe when there was diffuse in ltration of leukocytes throughout the submucosal layer; and 5, severe when there was diffuse in ltration with multiple necrotic foci.…”
Section: Histological Analysismentioning
confidence: 99%
“…[13][14][15][16][17][18] Recently, AuNPbased functionalized stents were introduced to locally treat cancer cells or tissue hyperplasia adjacent to stented non-vascular luminal organs. 11,12,19,20 Park et al have reported in rat models that locally applied temperature increases (50°C to 65°C) successfully suppressed tissue hyperplasia after esophageal and gastroduodenal stent placement. 11,20 We hypothesized that AuNP-coated SEMS could be used for localized PTT under NIR laser irradiation.…”
Section: Introductionmentioning
confidence: 99%